Legalisasi Ganja Medis di Indonesia: Potensi, Tantangan, dan Pendekatan melalui Penetapan Pengadilan - Hermansyah, Agung; Alamsyah, Alamsyah; Maryanto, Maryanto; Setiadi, Wicipto (Indonesian Journal Publisher, 2024)
This study examines the legality of using the cannabis plant as a herbal medicine in Indonesia, which presents a dilemma between its medicinal benefits and the risk of abuse. The purpose of this research is to analyze cannabis regulations in the context of Indonesian law and explore the possibility of using cannabis for medical purposes. The research is conducted through a normative approach, utilizing literature studies and secondary data from statutory regulations and court decisions. This study employs a normative legal research method with data collection techniques consisting of literature review and legal document analysis. The data analysis technique used is a descriptive qualitative analysis of relevant regulations, such as Minister of Health Regulation No. 5 of 2020 and Law No. 35 of 2009 on Narcotics. The research findings reveal that although more than 50 countries have adopted medical cannabis programs, Indonesia still classifies cannabis as a Schedule I narcotic, prohibited for use in public health services. This study also finds that the legalization of medical cannabis in Indonesia could be pursued through legal efforts in the judiciary by filing a court determination or submitting a judicial review of the related regulations to the Supreme Court in order to achieve legal certainty based on justice.